Female genital tuberculosis – still a common cause of primary amenorrhea in developing countries - Bettaiah, Ramesh; Daksha, Shraddha; Ghanti, Rachana; Balakrishnan, Dhivya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Primary amenorrhea is defined as, no menses by age 14yrs in absence of growth or development of secondary sexual characteristics and no menses by age 16yrs regardless of the presence of normal growth or development of secondary sexual characteristics. Although pulmonary tuberculosis remains the commonest and the most infectious type of tuberculosis, extra pulmonary tuberculosis is becoming more prevalent especially in young women throughout the world. We report a case of young woman presenting as primary amenorrhea apparently having no signs and symptoms of tuberculosis. 20 yrs old unmarried girl was referred for primary amenorrhea with normal secondary sexual characters and presence of uterus, tubes and ovaries on abdominal scan. Hormonal assay and karyotyping was normal. She had negative progesterone challenge test and estrogen progesterone challenge test. Diagnosis of genital tuberculosis was confirmed by diagnostic hysterolaparoscopy and positive tubercular polymerase chain reaction and culture. Hysterolaparoscopy is a key tool for confirmation of diagnosis in cases of primary amenorrhea when the dilemma exists.